2019
DOI: 10.1038/s41418-019-0413-7
|View full text |Cite
|
Sign up to set email alerts
|

CPAP promotes angiogenesis and metastasis by enhancing STAT3 activity

Abstract: Centrosomal P4.1-associated protein (CPAP) is overexpressed in hepatocellular carcinoma (HCC) and positively correlated with recurrence and vascular invasion. Here, we found that CPAP plays an important role in HCC malignancies. Functional characterization indicated that CPAP overexpression increases tumor growth, angiogenesis, and metastasis ex vivo and in vivo. In addition, overexpressed CPAP contributes to sorafenib resistance. Mechanical investigation showed that the expression level of CPAP is positively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…There is increasing evidence that angiogenesis is closely related to the malignancy of liver cancer [ 23 ]. Chen found that CPAP promotes angiogenesis and metastasis in hepatocellular carcinoma [ 24 ]. In pancreatic cancer, angiogenesis is an essential factor for tumor progression [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that angiogenesis is closely related to the malignancy of liver cancer [ 23 ]. Chen found that CPAP promotes angiogenesis and metastasis in hepatocellular carcinoma [ 24 ]. In pancreatic cancer, angiogenesis is an essential factor for tumor progression [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another is that targeted agents can feedback influence the activity of downstream and parallel bypass signaling pathways 40–42 . Dysregulated STAT3 signaling has been strongly implicated in tumorigenesis 43 . Nowadays studies highlight that STAT3 is activated in response to some antitumor agents, such as receptor kinase inhibitors or HDAC inhibitors 22,26 .…”
Section: Discussionmentioning
confidence: 99%
“…As an inflammatory cytokine, IL-6 is mainly derived from stromal cells such as macrophages and fibroblasts around the tumor, and it is not secreted or is rarely secreted by the tumor cells themselves [59,60]. IL-6, similar to TNF-α, promotes the transformation of noncancer cells into cancer stem cells [61] while regulating the biological activity of tumor cells, leading to cell proliferation or distant metastasis [62]. In addition, IL-6 promotes tumor development by enhancing the T cell-mediated immuneinflammatory response, regulating gene expression, and inhibiting apoptosis in the cell through the JAK-STAT signaling pathway [63,64].…”
Section: Changes In the Tumor Inflammatory Environmentmentioning
confidence: 99%